Lymphoma in a patient with rheumatoid arthritis receiving methotrexate treatment: successful treatment with rituximab. Issue 9 (1st September 2001) - Stewart, M; Malkovska, V; Krishnan, J; Lessin, L; Barth, W
Abstract : A 55 year old man with chronic lymphocytic leukaemia (CLL) and rheumatoid arthritis (RA), treated for four years with methotrexate (MTX), who developed a B cell non-Hodgkin's lymphoma (B-NHL), is described. The tumour was localised to the shoulder and axillary lymph nodes, and positive for Epstein-Barr viral antigens. After failure of radiation and chemotherapy, a complete remission was achieved with a combination of antibody treatment (rituximab) and EPOCH. The development of a second malignancy in a patient with RA receiving MTX has not been described before. The summation of T cell deficiencies induced by MTX, CLL, and RA may all have contributed to the development of the B-NHL.